THE EFFECT OF INVENTORY INTENSITY, AND LIQUIDITY ON TAX AGGRESSIVENESS ON FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Petronius Jekang; Aloisius Hama (Jurnal Mantik, 2022)
Tax evasion is a crime that violates Indonesian tax law. Because taxpayers are trying to minimize taxes owed in an illegal way. While in tax avoidance (tax avoidance) is a legal action that can be justified because it does not violate the law. An act of tax avoidance is said to be illegal if the transaction is carried out solely for the purpose of tax avoidance or the transaction does not have a good business purpose. This study aims to examine and analyze the effect of liquidity and inventory intensity on tax aggressiveness. The population used in this study are food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 period. The data analysis technique in this study used measuring instruments through SPSS and multiple regression analysis. Based on the data that has been collected and then tested on the problems using multiple regression models, it can be concluded as follows: Inventory intensity has no effect on tax aggressiveness in food and beverage manufacturing companies listed on the IDX. Liquidity has no effect on tax aggressiveness in manufacturing companies in the food and beverage sector listed on the IDX. Inventory intensity has no effect on tax aggressiveness in food and beverage sector manufacturing companies listed on the IDX. Liquidity has no effect on tax aggressiveness in manufacturing companies in the food and beverage sector listed on the IDX. Inventory intensity has no effect on tax aggressiveness in food and beverage sector manufacturing companies listed on the IDX. Liquidity has no effect on tax aggressiveness in manufacturing companies in the food and beverage sector listed on the IDX.